EXPERIMENTAL INVESTIGATION ON STUDYING THE FLEXURAL BEHAVIOUR OF GEOPOLYMER CONCRETE BEAM UNDER FIXED BOUNDARY CONDITION - Rajkannan, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Geo polymer concrete is one of the emerging construction material as a substitute for conventional cement concrete, eliminating the usage of OPC. This work is aimed to cast and testing of geo-polymer beam elements with restrained edge condition. The size of beam is 1m x 1m x 0.05 m. By using yield line theory, the moment of resistance and maximum deflection under flexural loading are calculated for the of GPC beam. Reinforcement details of these beam are calculated using ultimate load method as per IS code provisions. Geopolymer concrete is the greener concrete, which has the potential technology to reduce the carbon emission and lead to sustainable developments and growth of the concrete industry. During the manufacturing of ordinary Portland cement, large amount of carbon dioxide is released in the atmosphere causing not only air pollution but also highly responsible factor of global warming.